Programmable Construction of Peptide‐Based Materials in Living Subjects: From Modular Design and Morphological Control to Theranostics - Li, Li‐Li; Qiao, Zeng‐Ying; Wang, Lei; Wang, Hao (Advanced materials (Weinheim), 2019)
Self‐assembled nanomaterials show potential high efficiency as theranostics for high‐performance bioimaging and disease treatment. However, the superstructures of pre‐assembled nanomaterials may change in the complicated physiological conditions, resulting in compromised properties and/or biofunctions. Taking advantage of chemical self‐assembly and biomedicine, a new strategy of “in vivo self‐assembly” is proposed to in situ construct functional nanomaterials in living subjects to explore new biological effects. Herein, recent advances on peptide‐based nanomaterials constructed by the in vivo self‐assembly strategy are summarized. Modular peptide building blocks with various functions, such as targeting, self‐assembly, tailoring, and biofunctional motifs, are employed for the construction of nanomaterials. Then, self‐assembly of these building blocks in living systems to construct various morphologies of nanostructures and corresponding unique biological effects, such as assembly/aggregation‐induced retention (AIR), are introduced, followed by their applications in high‐performance drug delivery and bioimaging. Finally, an outlook and perspective toward future developments of in vivo self‐assembled peptide‐based nanomaterials for translational medicine are concluded. Taking inspiration from self‐assembly systems in nature, a new strategy of “in vivo self‐assembly” is proposed to in situ construct functional nanomaterials in living subjects. This concept, from the modular molecular design, assembly driving forces, morphology control, and biological effects to biomedical applications, is discussed.